P163 Tiotropium decreases the risk of exacerbations in patients with symptomatic asthma regardless of baseline characteristics including markers of allergic status. (14th November 2013) - Halpin, DMG; Bateman, ED; Tashkin, DP; Engel, M; Dahl, R; Paggiaro, P; Beck, E; Vandewalker, M; Seibold, W; Moroni-Zentgraf, P; Schmidt, H; Kerstjens, HAM
Abstract : Rationale: The addition of tiotropium provides bronchodilation and reduces exacerbations in patients with severe asthma (Kerstjens et al . NEJM 2012). Subgroup analyses were performed to determine whether this positive effect was limited to definable subgroups. Methods: Eligible patients: were aged 18–75 years; had a =5-year history of asthma; were diagnosed before the age of 40; scored =1.5 on Asthma Control Questionnaire 7; and were life-long non-smokers or ex-smokers (<10 pack-years) who quit smoking =1 year before study enrolment. Patients had experienced =1 exacerbation in the previous year. Time to first severe exacerbation from the pooled data after 48 weeks was one of three primary end points. Secondary end points included time to first episode of asthma worsening. Subgroup analyses of time to first severe exacerbation were performed in groups defined by baseline characteristics, including age, allergic status, smoking status and reversibility. Results: 912 patients were randomised: 456 received 5 µg tiotropium via Respimat ® Soft Mist™ Inhaler and 456 received placebo once daily for 48 weeks. In the total study group, the time to first severe exacerbation was increased by the addition of tiotropium (risk reduction 21%; hazard ratio 0.79; p = 0.03). The time to first episode of asthma worsening was increased in the tiotropium group compared with placebo (risk reduction 31%; hazard ratio 0.69; p < 0.001). Subgroup analyses showed that neither the time to first severe exacerbation (Figure) nor the time to first episode of asthma worsening was dependent on baseline characteristics (no significant interactions). Conclusions: The increase in time to first severe exacerbation and first episode of asthma worsening found with the addition of tiotropium was not limited to specific subgroups of patients, including some characteristics that are usually found in patients with chronic obstructive pulmonary disease, such as former smoking, non-allergic status or minimal reversibility. Tiotropium seems effective across a broad spectrum of patients with severe persistent asthma who remain symptomatic and experience exacerbations despite the combination use of moderate- to high-dose inhaled corticosteroids plus long-acting beta agonists.